A Small Group Activity About Bacterial Regulation And Complementation - Susan Merkel (American Society for Microbiology, 2010)
As teachers, we well understand the need for activities that help develop critical-thinking skills in microbiology. In our experience, one concept that students have difficulty understanding is transcriptional regulation of bacterial genes. To help with this, we developed and evaluated a paper-based activity to help students understand and apply the concepts of bacterial transcriptional regulation. While we don’t identify it as such, we use a complementation experiment to assess student understanding of how regulation changes when new DNA is introduced. In Part 1 of this activity, students complete an open-book, take-home assignment that asks them to define common terminology related to regulation, and draw the regulatory components of different scenarios involving positive and negative regulation. In Part 2, students work in small groups of 3–4 to depict the regulatory components for a different scenario. They are asked to explain the results of a complementation experiment based on this scenario. They then predict the results of a slightly different experiment. Students who completed the Regulation Activity did significantly better on post-test questions related to regulation, compared to pre-test questions.